Leadership and Economic Development of Ghana - Mensah , David Kwasi (Journal of Social Science Studies, 2021)
The relationship on leadership quality and its impact on skewed economic development in Ghana have been investigated. This investigation has been carried out in Ghana and its neighbouring countries that attained independence around the same time, under similar pattern of political governance. A comparative analysis is used to differentiate between these countries economic policies and their leadership styles used. It reveals that Ghana remains static and underdeveloped for many years despite changes in leadership and political governance. Evidently, while at the time of their independence, Ghana’s per capital income in 1960 was higher than Nigeria, India and Egypt. Ghana’s development has been sluggish whilst the rest of the countries have accelerated at a faster rate with fantastic economic policies combined with good leadership skills. The way forward towards establishing a sustainable economic development in Ghana includes vision, goals and value of the nation, a strategy for achieving, managing change and national transition.